Proceedings of the Web Conference 2020 2020
DOI: 10.1145/3366423.3380300
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Engagement with Citations on Wikipedia

Abstract: Wikipedia is one of the most visited sites on the Web and a common source of information for many users. As an encyclopedia, Wikipedia was not conceived as a source of original information, but as a gateway to secondary sources: according to Wikipedia's guidelines, facts must be backed up by reliable sources that reflect the full spectrum of views on the topic. Although citations lie at the heart of Wikipedia, little is known about how users interact with them. To close this gap, we built client-side instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 58 publications
3
42
0
Order By: Relevance
“…Wikipedia articles are created, improved, and maintained by the efforts of the community of volunteer editors (Chen & Roth, 2012;Priedhorsky, Chen, et al, 2007), and they are used in a variety of ways by a wide user base (Lemmerich, Sáez-Trumper, et al, 2019;Piccardi, Redi, et al, 2020;Singer, Lemmerich, et al, 2017). The information Wikipedia contains is generally considered to be of high quality and up to date (Adams et al, 2020;Geiger & Halfaker, 2013;Keegan, Gergle, & Contractor, 2011;Kumar, West, & Leskovec, 2016;Piscopo & Simperl, 2019;Priedhorsky et al, 2007;Smith, 2020), notwithstanding room for improvement and the need for constant knowledge maintenance (Chen & Roth, 2012;Forte, Andalibi, et al, 2018;Lewoniewski, Wę cel, & Abramovich, 2017).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Wikipedia articles are created, improved, and maintained by the efforts of the community of volunteer editors (Chen & Roth, 2012;Priedhorsky, Chen, et al, 2007), and they are used in a variety of ways by a wide user base (Lemmerich, Sáez-Trumper, et al, 2019;Piccardi, Redi, et al, 2020;Singer, Lemmerich, et al, 2017). The information Wikipedia contains is generally considered to be of high quality and up to date (Adams et al, 2020;Geiger & Halfaker, 2013;Keegan, Gergle, & Contractor, 2011;Kumar, West, & Leskovec, 2016;Piscopo & Simperl, 2019;Priedhorsky et al, 2007;Smith, 2020), notwithstanding room for improvement and the need for constant knowledge maintenance (Chen & Roth, 2012;Forte, Andalibi, et al, 2018;Lewoniewski, Wę cel, & Abramovich, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…The information Wikipedia contains is generally considered to be of high quality and up to date (Adams et al, 2020;Geiger & Halfaker, 2013;Keegan, Gergle, & Contractor, 2011;Kumar, West, & Leskovec, 2016;Piscopo & Simperl, 2019;Priedhorsky et al, 2007;Smith, 2020), notwithstanding room for improvement and the need for constant knowledge maintenance (Chen & Roth, 2012;Forte, Andalibi, et al, 2018;Lewoniewski, Wę cel, & Abramovich, 2017). Following Wikipedia's editorial guidelines, the community of editors creates content often relying on scientific and scholarly literature (Arroyo-Machado, Torres-Salinas, et al, 2020;Halfaker, Mansurov, et al, 2018;Nielsen, Mietchen, & Willighagen, 2017), and therefore Wikipedia can be considered a mainstream gateway to scientific information (Heilman, Kemmann, et al, 2011;Laurent & Vickers, 2009;Lewoniewski et al, 2017;Maggio, Willinsky, et al, 2019;Piccardi et al, 2020;Shafee, Masukume, et al, 2017). Unfortunately, few studies have considered the representativeness and reliability of Wikipedia's scientific sources.…”
Section: Related Workmentioning
confidence: 99%
“…Wikipedia articles are created, improved and maintained by the efforts of the community of volunteer editors [46, 10], and they are used in a variety of ways by a wide user base [52, 31, 44]. The information Wikipedia contains is generally considered to be of high-quality and up-to-date [46, 24, 18, 29, 45, 5, 53], notwithstanding margins for improvement and the need for constant knowledge maintenance [10, 32, 16].…”
Section: Related Workmentioning
confidence: 99%
“…Following Wikipedia’s editorial guidelines, the community of editors creates contents often relying on scientific and scholarly literature [40, 19, 6], and therefore Wikipedia can be considered a mainstream gateway to scientific information [30, 20, 32, 50, 34, 44]. Unfortunately, few studies have considered the representativeness and reliability of Wikipedia’s scientific sources.…”
Section: Related Workmentioning
confidence: 99%
“…One of the works used special identifiers (such as DOI, ISBN) to unify the references and find the similarity of sources between language versions of Wikipedia [12]. Another recent study analyzed engagement with citations in Wikipedia articles and found that references are consulted more commonly when readers cannot find enough information in selected Wikipedia article [13]. There are also works, which showed that a lot of citations in Wikipedia articles refers to scientific publications [12,14], especially if they are open-access [15], wherein Wikipedia authors prefer to put recently published journal articles as a source [16].…”
Section: Recent Workmentioning
confidence: 99%